Insufficient control of morning home blood pressure in Japanese patients with hypertension associated with diabetes mellitus - Uchida, Haruhito A. (Blackwell Publishing Ltd, 2010)
Aims/Introduction:  The combination of hypertension with diabetes mellitus (DM) has been recognized as a critical risk factor for cardiovascular disease (CVD). We investigated the blood pressure levels in hypertensive patients with DM (HDM patients) compared with those without DM (HnDM patients). Furthermore, we examined the effect of risk factors, including chronic kidney disease (CKD) and stroke, on the management of both office blood pressure (OBP) and morning home blood pressure (MHBP). Materials and Methods:  OBP and MHBP were evaluated in 1230 essential hypertensive patients in 30 institutions. Among them, 366 (30%) were complicated with DM. Results:  The ratio of masked hypertensives whose systolic OBP was <140 mmHg and systolic MHBP was more than 135 mmHg in HDM patients was significantly higher than that in HnDM patients (P < 0.02). HDM patients had significantly lower systolic and diastolic OBP and diastolic MHBP than HnDM patients (P < 0.05, respectively). However, systolic MHBP in HDM patients tended to be higher compared with HnDM patients (P = 0.0623). A stratified analysis showed that HDM patients with CKD or stroke had significantly higher systolic MHBP than others (P < 0.05, respectively). The adjusted odds ratio for morning hypertension defined by a systolic MHBP more than 135 mmHg was significantly higher in the HDM patients with CKD (1.98) compared with HnDM patients without CKD (reference). Conclusions:  Diabetes, CKD and stroke are risk factors for MHBP. More intensive treatment is needed to achieve the thera‐peutic goal for systolic MHBP in HDM patients, especially those who are complicated with CKD or stroke. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2010.00056.x, 2010).